Factor structure of the inventory of callous-unemotional traits in a representative sample of German 9th grade students - Kliem, Sören (Journal of abnormal child psychology, 2020)
Callous-unemotional (CU) traits represent the affective components of the psychopathy construct and show a strong relationship to violence and conduct-disorder in children. The Inventory of Callous-Unemotional Traits (ICU) is the current standard to assess CU traits. Despite the ICU having originally been constructed as a four-dimensional instrument, several studies found a three-factorial structure in combination with a general ICU-factor to be the best fitting factor-model. An imbalance in the number of positively and negatively worded items can be observed between the identified ICU dimensions. To investigate the effect of item keying on the factor structure we tested different factor-models in data stemming from a large sample (N = 3878) of German ninth grade students. Our findings suggest that the original four-factorial structure with a method factor shows good model fit. This solution is furthermore in line with the specifiers of the additional coding of Limited Prosocial Emotions for Conduct Disorder in the DSM-V.